Influence of Date of Transplanting on The Yield Performance of Salt Tolerant Rice Varieties During Boro Season - Akter, T (Bangladesh Agronomy Journal, 2025)
Future food security in Bangladesh relies heavily on effective adaptation strategies for dry-season Boro rice production in coastal regions. This study focused on yield performance by evaluating the different transplanting dates as an adaptation approach for dry-season Boro rice. An experiment was conducted in Kamargati village, Kaliganj upazila under Satkhira district to assess the effect of rice variety, transplanting date, and their interaction on the yield performance of salt-tolerant Boro rice during December 2023 to February 2024. The study included three varieties: BRRI dhan67, BRRI dhan97, and BRRI dhan99, with five transplanting dates: 15th December, 30th December, 15th January, 30th January, and 15th February. The experiment followed a split-plot design with three replications. Results showed that var. BRRI dhan67 yielded the highest grain (5.58 t ha−1) when transplanted on 15th December. In the transplanting from 15th to 30th December, BRRI dhan99 outperformed BRRI dhan97 in terms of yield. However, after 15th January, increasing soil and water salinity led to crop damage, resulting in no yield. The challenge of early transplantation arises due to the prevalence of T. Aman rice in the area, while late transplanting faces difficulties from increasing salinity in soil and water. The results indicate significant differences in yield based on the variety and planting date, with var. BRRI dhan67 consistently producing higher yields in early stages. Bangladesh Agron. J. 2024, 27(1): 19-22